Estimation of the Permeability of Rock Samples Obtained from the Mercury Intrusion Method Using the New Fractal Method - Kouqi Liu; Mehdi Ostadhassan (Fractal and Fractional, 2022)
Rock permeability, defined as the ability of fluid to flow through the rocks, is one of the most important properties of rock. Many researchers have developed models to predict the permeability of rock from the porosity and pore size based on the mercury intrusion. However, these existing models still have some limitations. In this study, based on data regarding the fractal nature of the mercury intrusion of the rocks, we built a new model to predict the permeability of the rocks. In order to verify the new model, we extracted data regarding different kinds of samples from the literature and estimated the permeability using the new model. The results showed that the model could predict various types of rocks, such as tight sandstone, carbonates, and shale. The comparison of the calculated permeability using the new model is closer to the measured value than the value estimated from the existing models, indicating that the new model is better in predicting the permeability of rock samples.